Development modeling of the Neft Dashlari field within the South Caspian Basin - Насібова, Гултар; Ганбарова, Шура (Київський національний університет імені Тараса Шевченка, 2026)
Background. The paper examines the current state of development of the productive horizons within the South Caspian Basin, focusing on Block IV of the Neft Dashlari field. As one of Azerbaijan's largest offshore fields, Neft Dashlari possesses significant hydrocarbon reserves. This study systematizes extensive geological and field data to provide a reliable description of the field's geological and technological characteristics, including stratigraphy, tectonics, fluid hydrochemistry, and current reserve status. Methods. The study is based on the analysis of historical production data since the field's discovery in 1949. Statistical and geological modeling was used to evaluate the 26 discovered oil-bearing layers. The research focuses on the distribution of industrially significant residual oil reserves within the upper and lower stages of the Productive Series (PS) sediments. Results. Since the commencement of operations, cumulative production has reached 168,787.1 thousand tons of oil, 243,913.2 thousand tons of total liquid, and 13,090.4 million cubic meters of dissolved gas. Current annual production stands at 812 thousand tons of oil with an average water cut of 38.2 %. The average daily well yield is 7.2 tons of oil and 11.7 tons of liquid. The utilization rate of recoverable reserves is 87.3 %. The current oil recovery factor (ORF) is 0.440, while the ultimate ORF is estimated at 0.504. To maintain pressure and enhance recovery, water injection has been employed since 1953, specifically targeting the VII and X horizons, as well as the Fasila and Kirmaki suites of Block IV. Conclusions. Development models for Block IV indicate that micellar flooding is a highly effective Enhanced Oil Recovery (EOR) method for extracting residual reserves. The use of microemulsions allows for the revitalization of flooded layers, potentially increasing the ORF to 50–60 %. Furthermore, it is recommended to increase reservoir sweep efficiency, reduce water cut, and optimize the well stock through sidetracking (drilling of lateral boreholes). To further enhance recovery at the final stage of development, the implementation of Water-Alternating-Gas (WAG) injection and the transfer of flooded wells to higher productive horizons are proposed.

Вступ. Присвячено аналізу сучасного стану розробки продуктивних пластів Південнокаспійської западини на прикладі IV блоку родовища Нефт Дашларі. Це одне з найбільших родовищ Азербайджану з потужними запасами вуглеводнів. У роботі систематизовано великий обсяг геолого-промислових даних, що дало змогу уточнити стратиграфічні, тектонічні та гідрохімічні характеристики об’єкта, а також оцінити його поточний стан. Методи. Дослідження базується на аналізі показників експлуатації 26 нафтових пластів, відкритих з 1949 р. Використано методи статистичного аналізу та геологічного моделювання для оцінки залишкових запасів нафти, які нині зосереджені переважно у верхніх та нижніх відділах Продуктивної товщі (ПТ). Результати. З початку розробки накопичений видобуток становив 168 787,1 тис. т нафти та 13 090,4 млн м³ розчиненого газу. Річний видобуток нафти становить 812 тис. т за середньої обводненості продукції 38,2%. Середньодобовий дебіт однієї свердловини становить 7,2 т нафти та 11,7 т рідини. Ступінь виробленості видобувних запасів сягає 87,3 %. Поточний коефіцієнт вилучення нафти становить 0,440, а кінцевий (проєктний) – 0,504. Для інтенсифікації видобутку з 1953 р. застосовується заводнення, зокрема на VII та X горизонтах, фасільській та кірмакійській свитах IV блоку. Висновки. На основі побудованих моделей розробки обґрунтовано доцільність застосування міцелярного заводнення для вилучення залишкових запасів. Використання мікроемульсій дає змогу відновити експлуатацію заводнених пластів і підвищити КВН до 55–60 %. Додатково рекомендовано збільшити охоплення пластів витісненням, впровадити заходи зі зниження обводненості та провести реконструкцію фонду свердловин шляхом буріння бокових стовбурів. Оскільки об’єкти перебувають на завершальній стадії розробки, запропоновано впровадження водогазового впливу та повернення свердловин на вищезалеглі об'єкти.
Моделювання розробки родовища Нефт Дашларі в межах Південнокаспійського басейну
Keywords: oil recovery factor; exploitation; water injection method; development indicators of the horizons; oil production; gas production; development rate; коефіцієнт вилучення нафти; розробка; спосіб закачування води; показники розробки горизонтів; видобуток нафти; видобуток газу; швидкість розробки